2006
DOI: 10.1002/bdrb.20092
|View full text |Cite
|
Sign up to set email alerts
|

Artesunate-induced depletion of embryonic erythroblasts precedes embryolethality and teratogenicity in vivo

Abstract: In summary, embryonic erythroblasts are the primary target of ART toxicity in the rat embryo after in vivo treatment, preceding embryolethality and malformations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 39 publications
4
70
0
Order By: Relevance
“…A summary of the research findings and possible mechanisms of artemisinin drugs in the embryotoxicity studies in vitro and in vivo (Clark et al, 2009;Efferth & Kaina 2010;Finaurini et al, 2010;Longo et al, 2006aLongo et al, , 2006bLongo et al, , 2008Wartenberg et al, 2003;White et al, 2008) 2.2.1 Inhibitory effects of AS/DHA on hematopoiesis AS is embryolethal and teratogenic in rats, with a very narrow window of sensitivity between days 10-14 of gestation (Clark et al, 2004;Li et al, 2009;White et al, 2006). Further studies with a single oral dose of 17 mg/kg AS on gestational day (GD) 10-11 demonstrated that a paling of the visceral yolk sacs was observed within 3-6 hr after treatment.…”
Section: As/dha Therapy Causes Erythrocyte Depletion and Resulting Emmentioning
confidence: 99%
See 3 more Smart Citations
“…A summary of the research findings and possible mechanisms of artemisinin drugs in the embryotoxicity studies in vitro and in vivo (Clark et al, 2009;Efferth & Kaina 2010;Finaurini et al, 2010;Longo et al, 2006aLongo et al, , 2006bLongo et al, , 2008Wartenberg et al, 2003;White et al, 2008) 2.2.1 Inhibitory effects of AS/DHA on hematopoiesis AS is embryolethal and teratogenic in rats, with a very narrow window of sensitivity between days 10-14 of gestation (Clark et al, 2004;Li et al, 2009;White et al, 2006). Further studies with a single oral dose of 17 mg/kg AS on gestational day (GD) 10-11 demonstrated that a paling of the visceral yolk sacs was observed within 3-6 hr after treatment.…”
Section: As/dha Therapy Causes Erythrocyte Depletion and Resulting Emmentioning
confidence: 99%
“…In rats these findings were attributed to cell death resulting from anemia and hypoxia (Longo et al, 2006a); here, frog larvae death may be secondary to anemia. Potentially larvae death may not be mediated by cell death but rather by altered intracardiac hemodynamics due to RBC degeneration, as speculated by White et al (2006). In embryotoxicity studies conducted with DHA administered at GD 9, the yolk sac was shown to be fully vascularized.…”
Section: Antivasculogenic and Antiangiogenic Effects Of As/dhamentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, several studies showed that ART could inhibit the growth of various carcinoma cell lines [1][2][3] and suppress tumor cell proliferation by inducing apoptosis, 4 indicating that ART may be a promising novel candidate for leukemia therapy. However, a variety of lines of evidence indicate that ART inhibited cell proliferation in a dose-dependent manner, and a high concentration of ART induced embryo toxicity, [5][6][7] reversible renal damage toxicity, 8 and toxicity to bone development, 9 which limit the usefulness of ART. To minimize side effects associated with dosage during chemotherapy, a promising approach is to combine a conventional chemotherapy with new strategies to maximize efficacy of tumor treatment through inducing cell apoptosis.…”
Section: Introductionmentioning
confidence: 99%